Effect of Duct Height on the Magnitude of Acoustic Resonance for Single Cylinder in Cross-flow - Afifi, Omar; Mohany, Atef (Canadian Acoustics, 2017)
Flow-excited acoustic resonance in industrial applications, such as tube bundles of heat exchangers is a major concern due to its harmful effects. If not treated, flow-excited acoustic resonance may lead to excessive vibrational loads on the tube bundles, which could subsequently result in structural failure and critical equipment damage. In this paper, the effect of the duct height on the self-excited acoustic resonance mechanism of single cylinders in cross-flow is experimentally investigated for the first acoustic cross mode. Three duct heights of 203, 254 and 305 mm and seven cylinders of diameters in the range between 10.56 – 28.5 mm are used in the investigation. Changing the height of the duct changed the frequency coincidence at which resonance occurred, thus the acoustic damping and stiffness of the system were changed. It was found that as the duct height increases, the stiffness of the system decreases, and the system becomes weaker and more susceptible to acoustic resonance. Moreover, increasing the duct height was found to decrease the acoustic damping of the system, which changed the magnitude of the acoustic pressure amplitudes at resonance, even when the dynamic head at coincidence is the same. The acoustic attenuation, due to the visco-thermal losses, for each duct was quantified theoretically by adapting the Kirchhoff acoustical damping model which takes into account the geometrical aspects of the duct. The results of experiments discussed in this paper shows that the damping of the duct is an important parameter that should be included in prediction criteria proposed for complex geometries such as tube bundles of heat exchangers.